Implementation of Science Student Worksheets Based on Multiple Intelligences Material Temperature and Its Changes - Silalahi, Maria; Afrida, Afrida (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
The aim of this research is to produce science worksheets based on multiple intelligences on temperature and its changes, then to find out students' responses to science worksheets based on multiple intelligences. The research method used is the Research and Development (R&D) method and uses the Borg and Gall development model. The test subjects in this research were students at SMPN 1 Jambi City. The instruments used in this research were an expert team validation questionnaire and a student perception questionnaire. The data analysis technique for the expert team's validation questionnaire carried out a structured assessment, while for validator suggestions used qualitative descriptions. The data analysis technique for student questionnaires is carried out using a rating scale which is then interpreted in a qualitative sense. From the research results, the results of the student perception questionnaire regarding the worksheets that had been tested were an average of 82% which could be categorized as "very good". Based on the results obtained, it can be concluded that the Science Worksheet Based on Multiple Intelligences on temperature and its changes in class VII is very good to use as supporting teaching material for teachers and students in the integrated science learning process in the classroom.